Homogenize Strain Distribution via Molecular Network Engineering for Mechanically Reliable Flexible Perovskite Solar Cells - Han, Fuhao; Zhang, Zuhong; Wu, Hongzhuo; Yuan, Hongxing; Lu, Linfeng; Su, Zhenhuang; Gao, Xingyu; Cao, Qi; Li, Zhihao (Nano-Micro Letters, 2026)
Flexible perovskite solar cells (FPSCs) suffer from strain localization-induced mechanical degradation, primarily due to heterogeneous strain distribution at grain boundaries. Herein, we propose a molecular engineering approach involving a crosslinked Methacrylic anhydride (MA) to construct a 3D crosslinking network within perovskite films. This molecular-scale network effectively redistributes localized strain into a more homogeneous pattern, as indicated by reduced strain variance and a lower Young’s modulus. Simultaneously, the MA network modulates crystallization kinetics, leading to enlarged grain sizes, enhanced (001) orientation, and decreased defect density. Together, these effects minimize strain concentration and promote elastic strain release, thereby suppressing microcrack formation at grain boundaries. As a result, the optimized rigid perovskite solar cells exhibit superior conversion efficiency of 26.42%, while the FPSCs reach 25.03% with excellent mechanical stability. Highlights: 1 Dual-function molecular ligand (MA) can coordinate with Pb2+ to passivate defect at grain boundaries and undergoes in-situ polymerization to form a stress-buffering network. 2 Attributing to the simultaneous defect suppression and strain homogenization, the MA-modified perovskite solar cells demonstrate high photovoltaic performance with power conversion efficiency up to 26.42% (rigid) and 25.03% (flexible). 3 The MA-modified devices demonstrate excellent stability under various environmental stress conditions, including thermal aging, light irradiation, and bending.